Documenting and Transmitting Intangible Cultural Heritage through Documentary Film - Basanbayar , Buyannemekh (Mongolian Journal of Arts and Culture, 2025)
This study examines the significance of documenting and safeguarding intangible cultural heritage through documentary film, using “Altan tulga, mungun totgo, which depicts the wedding rituals of the Zakhchin ethnic group, as the primary research material. The study regards documentary film not merely as a medium for transmitting information, but as a potential visual (audiovisual) document for recording and preserving cultural heritage. The findings demonstrate that the documentary serves as an important ethnographic source that documents the structure, symbolism, and ritual practices of Zakhchin wedding rituals within their authentic social context. Furthermore, the study reveals that documentary film has tangible potential to support the intergenerational transmission of intangible cultural heritage. It also clarifies that prior scholarly research on specific ethnic groups constitutes a crucial theoretical and methodological foundation for the production of ethnographic documentary films. Баримтат киногоор соёлын өвийг баримтжуулан уламжлуулах нь Хураангуй: Захчины хуримын зан үйлийг дүрсэлсэн “Алтан тулга, мөнгөн тотго” баримтат киног судалгааны хэрэглэгдэхүүн болгон сонгож, соёлын биет бус өвийг баримтат киногоор дамжуулан баримтжуулах, хадгалан хамгаалах ач холбогдлыг шинжиллээ. Ингэснээр баримтат киног зөвхөн мэдээлэл дамжуулах хэрэгсэл төдий бус, харин соёлын өвийг бүртгэх, хадгалах визуал (аудиовизуал) баримт бичиг болох боломжтой гэж үзэж байна. Судалгааны үр дүнд уг баримтат кино нь захчины хуримын зан үйлийн бүтэц, бэлгэдэл, ёс горимыг бодит нөхцөлд нь баримтжуулсан угсаатны зүйн судалгааны чухал эх сурвалж болохын зэрэгцээ соёлын биет бус өвийг өвлүүлэн уламжлуулахад дэмжлэг үзүүлэх бодит боломжтойг харууллаа. Түүнчлэн угсаатны бүлгийн зан заншил, ёс уламжлалыг баримтат кино хэлбэрээр бүтээн туурвихад тухайн угсаатны талаар хийгдсэн өмнөх судалгаанууд онол, арга зүйн чухал суурь болдгийг тодруулж байна. Түлхүүр үгс: захчин хурим, хуримын зан үйл, соёлын биет бус өв, баримтат кино